2022
DOI: 10.3389/fbioe.2022.961898
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity pulsed ultrasound promotes periodontal regeneration in a beagle model of furcation involvement

Abstract: Objective: To evaluate the regeneration potential of periodontitis tissue treated by low-intensity pulsed ultrasound (LIPUS) combined with the guided tissue regeneration (GTR) technique in a beagle model of furcation involvement (FI).Background: Achieving predictable regeneration remains a clinical challenge for periodontitis tissue due to the compromised regenerative potential caused by chronic inflammation stimulation. LIPUS, an FDA-approved therapy for long bone fracture and non-unions, has been demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In the field of stem cell research, LIPU promotes the expansion, differentiation, and migration of mesenchymal stem cells [ 29 , 30 ], and it has been reported that LIFU-induced BBB regulation can promote neurogenesis through the activation of endogenous neural stem cells [ 31 ]. In addition, LIPU can produce different biological effects on organs, tissues, and cells, and can be applied in fracture healing, cartilage repair [ 32 ], periodontal tissue regeneration [ 33 ], and alveolar bone regeneration [ 34 ]. In human studies, transcranial FUS inhibits the brain electrical activity evoked by somatosensory evoked potentials (SEPs) induced by median nerve stimulation in the primary somatosensory area [ 35 , 36 ].…”
Section: Clinical Application Of Fus In the Treatment Of Pdmentioning
confidence: 99%
“…In the field of stem cell research, LIPU promotes the expansion, differentiation, and migration of mesenchymal stem cells [ 29 , 30 ], and it has been reported that LIFU-induced BBB regulation can promote neurogenesis through the activation of endogenous neural stem cells [ 31 ]. In addition, LIPU can produce different biological effects on organs, tissues, and cells, and can be applied in fracture healing, cartilage repair [ 32 ], periodontal tissue regeneration [ 33 ], and alveolar bone regeneration [ 34 ]. In human studies, transcranial FUS inhibits the brain electrical activity evoked by somatosensory evoked potentials (SEPs) induced by median nerve stimulation in the primary somatosensory area [ 35 , 36 ].…”
Section: Clinical Application Of Fus In the Treatment Of Pdmentioning
confidence: 99%
“…LIPUS has been increasingly studied in the field of tissue regeneration in recent years, and its mechanisms in bone regeneration and inflammation control have been considerably explored. Wang et al (2022b) observed through an in vivo experimental study that LPIUS promotes new bone formation in the setting of periodontitis. In addition, they found that LIPUS is also effective in reducing inflammation and promoting angiogenesis, thus providing a favorable microenvironment for periodontal regeneration.…”
Section: The Mechanisms Of Lipus In Treating Experimental Periodontitismentioning
confidence: 99%
“…32,104 Therefore, large animal models such as canine and swine are needed for further in vivo validation of ASA@tHALLG nanocomposites targeting periodontal regeneration in the future. [105][106][107]…”
Section: Dovepressmentioning
confidence: 99%